PENGUATAN EKONOMI MASYARAKAT BERBASIS KELOMPOK - Mochamad Ridwan (Muhammadiyah University Press, 2012)
This study aims to make a synthesis related to efforts to develop an alternative modeling of the process of strengthening (empowering) the economy of poor coastal communities through the optimization of the group's role as the basis for economic development towards greater prosperity. Two programs of empowerment that are assessed Coastal Community Economic Empowerment Program and Program of Revenue Improvement for Small Farmers and Fishermen. To analyze the data has been collected, used four methods: Multiple Linear Regression Method, Path analysis, Structural Equation Model, and Descriptive Method (What-If Analysis). The results showed that alternative models that have been synthesized assume important roles in the group as a strategic base on the effectiveness of the program, besides the influence of internal and external factors, which are both strongly associated with quality resources and local knowledge of each area/coastal areas where the coastal areas tend to one another there is a difference.